2016
DOI: 10.22436/jmcs.016.01.08
|View full text |Cite
|
Sign up to set email alerts
|

The Heun Equation and Generalized Sl(2) Algebra

Abstract: In this paper, first we introduce the Heun equation. In order to solve such equation we show the generators of generalized sl(2). Second, we arrange the Heun equation in terms of new operators formed of generalized sl(2) generators and it's commutator relation. Here, instead of J + (r), J − (r) and J 0 we use the P + (r), P − (r) and P 0 (r) as operators of generalized sl(2) algebra. This correspondence gives us opportunity to arrange the parameters α and β in P 0 (r). Also, the commutator of such operators le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…This means that in the model under consideration the pseudoscalar fieldΦ is described by the Fuchstype function with the parameters (81). Also this function can be indicated as generalized Heun's function (see, e.g., [49] and references therein); the corresponding equations are well studied in the context of searching for generalized spherical wave functions. Typical sketches for the fundamental solutions Y (1) (x) and Y (2) (x) are presented in Figs.1 and 2.…”
Section: B Remark Concerning the Fuchs-type Functionsmentioning
confidence: 99%
“…This means that in the model under consideration the pseudoscalar fieldΦ is described by the Fuchstype function with the parameters (81). Also this function can be indicated as generalized Heun's function (see, e.g., [49] and references therein); the corresponding equations are well studied in the context of searching for generalized spherical wave functions. Typical sketches for the fundamental solutions Y (1) (x) and Y (2) (x) are presented in Figs.1 and 2.…”
Section: B Remark Concerning the Fuchs-type Functionsmentioning
confidence: 99%
“…In the presented work we made the first step in the analysis of the magnetic field restructuring driven by the interaction of the dipolar magnetic field with the axionic dark matter, which surrounds the star. We analyzed the solutions to the equations of magnetoelectro-axiono-statics in the static gravitational field of the Reissner-Nordström type; it was shown that the key equations for this model can be reduced to the Heun and Fuchs equations, which are known in mathematical physics [34][35][36][37]. Important detail of this analysis is that three dimensionless guiding parameters of the model happen to be encoded in the structure of the distorted halo of the axionic dark matter: we mean the parameter a = r− r+ , describing the relative depth of the inner and outer horizons of the magnetic star, and the parameters ω and Ω introduced by (80), which describe the effectiveness of the axion-photon coupling at the presence of the dipolar magnetic field.…”
Section: Discussionmentioning
confidence: 99%
“…Let us compare (66) with the Heun equation [34,35], which is a particular case of the known Fuchs equation [36,37]:…”
Section: Key Equationmentioning
confidence: 99%
“…(see, e.g., [51,52]), which is in its turn the particular case of the Fuchs equation [53,54]. The solution of this equation is regular at infinity, when ǫ+γ+δ = α+β+1.…”
Section: A the Heun Equationmentioning
confidence: 99%